Abbasid Policy and Its Economic Impact on the Livelihoods of Iraqi Scholars (132-334 AH/749-945 AD) - Prof. Dr. Mohammed Ali Ismail Weis (Journal of College of Education, 2025)
The research sheds light on the standard of living of the scholars of Iraq in the first Abbasid era (132-334AH/749-945AD), which is determined by the nature of the professions and jobs they hold, some of the scholars who held official state jobs, some of them practiced private professions , and their work in these various jobs was linked to their proximity to the caliphs and their dependence on them, Some scholars enjoyed wealth and luxury in the practice of their social life, which was afraid of the power of the scholars over the street, so he involved them in all state functions, and on the contrary, others lived in poverty and need after the state confiscated their properties and stripped them of the means and means of livelihood simply because they questioned loyalty or contributed to the victory of the street over the caliph, From this we see that the standard of living was not stable at a certain level, as sometimes it was high and other times it was low due to the nature of the work and the impact of the economic conditions on them.                                    The research was divided into two sections and a conclusion. The first section dealt with the living conditions of Iraqi scholars and their variation between poverty and wealth, and the second section dealt with the occupation of state jobs as a means of earning a living, such as the ministry, the judiciary, writing and others.         The study concluded that the political conditions greatly influenced the economic conditions of the Iraqi scholars, which had amajor changing in the economic life course of  scientists in general.
Keywords: Abbasi , livelihood, politics , economics, scholars